The EU’s Paternalistic Approach to the Integration of the Western Balkans – Border Disputes as a New Conditionality: Case of Prevlaka - Srdjan Orlandic (Romanian Journal of European Affairs, 2019)
In February 2018, the European Union (EU) announced the Strategy for the Western Balkans’ European integration that introduced a new momentum in the conditionality policy, which has the potential to decisively impact the pace and success of enlargement process. That addition to the conditionality policy concerns requirement to settle any open border issues prior to accession to the EU. Thus, this paper is assessing how border disputes could impact the integration processes of countries of the region in the light of the new conditionality. In addition, it will discuss one particular open border dispute in the Western Balkans involving the most advanced candidate country in the accession process (Montenegro) and the youngest member country (Croatia) over the Prevlaka peninsula.